2010
DOI: 10.1111/j.1600-0625.2010.01129.x
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of stress‐induced matrix metalloproteinase‐9 by Sirt1 in skin tissue

Abstract: Solar ultra-violet (UV) radiation and the ensuing photo-damage are adverse factors affecting human skin directly exposed to the sun. Stress responses induced by UV radiation (UVR) elicit premature skin ageing (photoageing), resulting in extensive damage to dermal connective tissue. Disruption of the normal dermal structure of skin connective tissue, primarily collagen, impairs a variety of skin functions and is considered to be the main cause of wrinkle formation. Matrix metalloproteases (MMPs) may be responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 37 publications
1
33
0
Order By: Relevance
“…7,15) In line with this, modulation of MAPK activity, especially p38 MAPK by number of small molecules has been suggested to be a possible strategy to suppress the induction of MMP-9 after stress conditions. 15,16) During the screening of plant extracts using MMP-9 inhibition assay, the extract of Citrus unshiu (SWINGLE) MARCOW (Rutaceae) peel was found to inhibit MMP-9 expression.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…7,15) In line with this, modulation of MAPK activity, especially p38 MAPK by number of small molecules has been suggested to be a possible strategy to suppress the induction of MMP-9 after stress conditions. 15,16) During the screening of plant extracts using MMP-9 inhibition assay, the extract of Citrus unshiu (SWINGLE) MARCOW (Rutaceae) peel was found to inhibit MMP-9 expression.…”
mentioning
confidence: 91%
“…7,12) In special, MMP-9 expression is dependent upon activator protein 1 (AP-1) transcriptional activity, 13) which is regulated by mitogen activated protein kinases (MAPKs).…”
mentioning
confidence: 99%
“…Resveratrol, a natural product-derived polyphenolic compound, has been widely used in the cosmetics and pharmaceutical industries because of its pharmacological activities, which include antitumor, anti-inflammation, and anti-aging effects . Recent reports have shown that resveratrol produced therapeutic effects against hyperplastic skin disorders by inhibiting keratinocyte proliferation , inhibited skin photoaging by acting as a Sirt-1 agonist (Lee et al, 2010), and showed anti-cancer effects in human melanoma cell lines (Niles et al, 2003). The anti-melanogenic effects of resveratrol and resveratrol analogs have already been reported by many other groups (Ohguchi et al, 2003;Song et al, 2012;Bae et al, 2013;Park and Boo, 2013;Park et al, 2014).…”
Section: Introductionmentioning
confidence: 76%
“…Their increased expression will cause an extracellular matrix metabolism disorder, leading to ventricular remodeling. Evidence shows that MMP-1 and MMP-3 expression is increased after siRNA silencing of the SIRT1 gene, whereas SIRT1 agonists suppress the elevation in MMP-1 [91,92]. Resveratrol can activate SIRT1 and thereby inhibit MMP-9 expression [91,92].…”
Section: Anti-myocardial Remodeling Effectmentioning
confidence: 95%